A watershed year : anatomy of the Iowa floods of 2008 - Mutel, Cornelia Fleischer (Bur oak book., 2010)
In June 2008, the rivers of eastern Iowa rose above their banks to create floods of epic proportions; their amazing size-flowing in places at a rate nearly double that of the previous record flood-and the rapidity of their rise ruined farmlands and displaced thousands of residents and hundreds of businesses. In Cedar Rapids, the waters inundated more than nine square miles of the downtown area; in Iowa City, where the flood was also the most destructive in history, the University of Iowa's arts campus was destroyed. By providing a solid base of scientific and technical information presented wi.